Metadata Quality and Academic Visibility Associated with Document Type Coverage in Institutional Repositories of Peruvian Universities - Alhuay Quispe, Joel (2017)
This article analyzes level of metadata quality (MQ ratio) and level of academic visibility in Google Scholar (IGS ratio) associated with coverage of four types of documents (theses, articles, books, and conferences) in repositories of Peruvian universities. This research is a cross-sectional descriptive and correlational study with intentional non-probabilistic sampling that analyzes 48 repositories from national (n = 10) and private (n = 38) universities integrated in the Peruvian National Digital Repository Alicia (alicia.concytec.gob.pe). Regarding the MQ ratio, we found a median of 0.67 [RIC: 0.552–0.891] for national universities and a median of 0.65 [RIC: 0.407–0.838] for private universities (p = .542). Regarding the IGS ratio, we found a median of 0.32 [RIC: 0.241–0.596] for national universities and a median of 0.62 [RIC: 0.464–0.749] for private universities (p = .054). The p value in Spearman's rank correlation shows a moderate correlation (ρ = 0.594; p < .01) between MQ ratio and the thesis coverage indicator, and a low correlation (ρ = 0.157) between the index of document indexing in Google Scholar and the proportion of documents harvested in Alicia. We conclude that the highest proportion of academic visibility is concentrated in private universities, and the metadata quality number of items integrated in Alicia favors public universities.